Success predictors of selective laser trabeculoplasty in primary angle-closure glaucoma: a long-term follow-up - N. I. Kurysheva; L. V. Lepeshkina; E. O. Shatalova (Российский офтальмологический журнал, 2019)
Purpose. To evaluate the effectiveness and the factors predictive of long-term failure of selective laser trabeculoplasty (SLT) in patients with the initial stage of primary angle-closure (PACG) and primary open angle glaucoma (POAG).Materials and methods. 65 PACG patients (65 eyes) and 65 POAG patients (65 eyes) were observed for 6 years. SLT was considered to be successful if its hypotensive effect consisted in an IOP decrease ³ 20 % achieved without any additional hypotensive treatment by antiglaucoma drop instillations or any hypotensive intervention (repeated SLT, antiglaucoma surgery, cataract phacoemulsification). The effectiveness was assessed using the Kaplan — Meier survival analysis. To determine the factors predictive of SLT, one-factor Cox proportional hazards regression analysis was used. Results. The hypotensive effect of SLT achieved was, for PACG and POAG, respectively, (1) 82 and 84 % one year after surgery; (2) 62 and 68 % two years thereafter, (3) 59 and 63 %, three years thereafter, (4) 34 and 42 %, four years thereafter, (5) 26 and 38 %, five years thereafter, (6) 4 and 8 % thereafter (log rank test, p = 0.234). The predictors of SLT failure were common for both forms of glaucoma in Cox regression analysis, namely: initial IOP > 24 mm Hg (OR = 1.184, p = 0.029 for PACG and OR = 1.156, p = 0.010 for POAG), corneal hysteresis < 9,5 mm Hg (OR = 1.441, р = 0.022 for PACG and OR = 1.486, р = 0.030 for POAG), corneal thickness < 540 μm (OR = 1.586, р=0.021 for PACG and OR =1.648, p =0.030 for POAG), reduced thickness of the retinal nerve fiber layer < 90 μm (OR = 1.231, p = 0.014 for PACG and OR =1.194, p = 0.027 for POAG) and age > 68 years (OR = 1.162, p = 0.040 for PACG and OR = 1.167, p = 0.000 for POAG). The additional failure predictors for PACG were the span of exposure to SLT < 180 0 (OR = 1.686, p = 0.004) and lens thickness > 4.86 mm (OR = 4.841, p = 0.001). Hypertension, diabetes mellitus, trabecular pigmentation degree and the type of antiglaucoma drugs taken before SLT were not found to be significant predictors of SLT effectiveness.Conclusion. SLT is an effective method of treating initial POAG and PACG after laser iridotomy. The long-term effect of SLT in both forms of glaucoma is affected by the initial IOP, glaucoma stage, and the patient’s age. The most important role in PACG is played by the span of SLT exposure and the size of the lens..